Simple consolidation method for dredger fill treatment using plastic vertical drains with vacuum. Issue 8 (14th September 2019) - Yonghui, Chen; Geng, Chen; Cheng, Xiao; Qi, Changguang
Abstract: Vacuum preloading with plastic vertical drains has been applied widely to accelerating consolidation of dredger fills. As a result of nonlinear variations in permeability and compression during the process of dredger fill consolidation, an axisymmetric consolidation method for dredger fill treatment using PVD with vacuum is proposed with varied R u . The effects of Cc / Ck and the loading ratio on the proposed method are discussed. It is found that the difference between the traditional method and proposed method is obvious in the case of large loading ratio (such as dredger fill treated with vacuum preloading). The degree of consolidation in the early phase of consolidation obtained using the proposed method was less than that obtained using the traditional method and the degree of consolidation in the later phase of consolidation obtained using the modified expression was larger than that obtained using the traditional method, as Cc /Ck < 1. However, opposite trends were observed when Cc /Ck > 1, the proposed method was closer to the actual situation. The applicability of the proposed method was verified by laboratory and field tests. For the consolidation of dredger fill with high water content, we recommend the adoption of the proposed method for calculating the degree of consolidation.